The Effect of an Inquiry Learning Model Assisted by Card Games on Fifth-Grade Students’ Understanding of Food Chain Concepts - Nursia Brongkos; Sirojjuddin Sirojjuddin; Mivtha Citraningrum (Lembaga Bale Literasi, 2026)
This study aims to determine the effect of an inquiry learning model assisted by card games on fifth-grade students’ understanding of food chain concepts at SD Negeri 21 Kota Sorong. The problem underlying this research is the low level of students’ conceptual understanding due to learning that is still conventional and does not actively involve students in the learning process. This study employed a quantitative approach with a quasi-experimental design in the form of a pretest-posttest control group design. The research sample consisted of two classes, each with 25 students, namely the experimental group and the control group. The instrument used was a multiple-choice test to measure students’ conceptual understanding. The results showed that the average posttest score of the experimental group (82.5) was higher than that of the control group (68.3). The results of the independent sample t-test showed a significance value of 0.000 < 0.05, indicating a significant effect of the inquiry learning model assisted by card games on students’ conceptual understanding. In addition, the improvement in learning outcomes, as shown by the gain score, was also higher in the experimental group than in the control group. Based on these findings, it can be concluded that the inquiry learning model assisted by card games is effective in improving students’ understanding of food chain concepts. The implications of this study indicate that the use of innovative learning models and interactive media can improve the quality of science learning in elementary schools and can serve as an alternative learning strategy that is more effective and meaningful.